What determines the crime rate? A macroeconomic case study - Tomas Karpavicius; Andriy Stavytskyy; Vincentas Rolandas Giedraitis; Erstida Ulvidiençe; Ganna Kharlamova; Brigita Kavaliauskaite (Economies, 2024)
This study examines the relationship between economic indicators and crime rates in six European countries: Lithuania, Germany, Greece, Portugal, Finland and Sweden. By examining macroeconomic factors such as GDP, security spending and per capita consumption, the study aims to understand how these variables affect crime dynamics. Using robust econometric techniques, including panel regression with fixed effects, the study identifies significant correlations and patterns. The findings reveal that the crime rate has a high degree of inertia and is significantly influenced by the previous level. Contrary to expectations, increased per capita consumption is associated with higher crime rates, which may indicate that wealthier societies are experiencing an increase in economic crime. Furthermore, higher spending on security does not necessarily reduce crime, suggesting that types of crime evolve as detection capabilities improve. This study highlights the complexity of the nexus between crime and the economy, highlighting the need for multifaceted, long-term policies to effectively combat crime and increase public safety. The results offer valuable insights for policymakers to develop comprehensive crime prevention and economic development strategies.
Keywords: 330; crime index; Finland; GDP share of security spending; Germany; Greece; Lithuania; per capita consumption; Portugal; regression; Sweden